Pengaruh medan magnet pada sifat fisis air sebagai media pertumbuhan sayuran kangkung dengan sistem hidroponik - Nursilmi, Nursilmi (Maliki Interdisciplinary Journal, 2024)
The term magnetic field also refers to the area (space) around a magnet that is affected by magnetic forces. This research uses a magnetic field produced by a magnetic tube with a current of 1A. Water was used as a research sample because it is an important substance for living things. The aim of this research is to determine the effect of magnetically treated water on the growth of vegetable seeds and the physical properties of water (eg pH) when growing plants using a hydroponic system. (Temperature, Conductivity) Research shows that water treated with magnetic fields has a lower pH and lower conductivity. This is because the magnetic field can exert a force on the movement of charges. The magnitude of the force acting on a moving charge depends on the strength of the field influenced by the charge. Pure water promotes the growth of kale. The temperature and conductivity of the treated water are ideal for a variety of vegetables.